Investigation of flow dynamics of wastewater in a pilot-scale constructed wetland using radiotracer technique. (May 2019) - Goswami, S.; Pant, H.J.; Poswal, D.; Samantray, J.S.; Asolekar, S.R.
Abstract: Constructed wetlands (CWs) are used for the treatment of wastewater by natural processes. Knowledge of the flow dynamics of wastewater through the CWs is required to evaluate their performance, operation and design. The residence time distribution (RTD) approach was used to evaluate the above-mentioned parameters in a CW. The RTD of wastewater flowing through a pilot-scale CW was measured using Technetium-99 m ( 99m Tc) as a radiotracer. The measured data were analyzed, and mean residence time and stagnant volumes were quantified under different operating conditions. A plug flow component in series along with a tank-in-series model with an exchange between the active and dead zones was used to simulate the measured RTD curves and investigate the flow dynamics of the flowing wastewater. The results of the study showed that the optimum flow rate and wastewater level in the CW was 2.3 m 3 /s and 0.6 m, respectively. Moreover, the results of the study will help in the operation and design of the existing wetland and design of new wetlands. Highlights: RTD measurements were carried out in a CW using the radiotracer technique. Technetium-99 m as sodium pertechnetate was used as the radiotracer. Flow fractions across different transacts of the wetland were estimated. Mean residence time, dead volume, and hydraulic efficiency were quantified. A model was conceptualized and used to simulate the experimental data.